2021
DOI: 10.1039/d1nr02037d
|View full text |Cite
|
Sign up to set email alerts
|

A silicon-based PbSe quantum dot near-infrared photodetector with spectral selectivity

Abstract: Traditional photodetectors usually respond to photons larger than the bandgap of a photosensitive material. In contrast to traditional photodetectors for broad-spectrum detection, the currently reported PbS/PMMA/PbSe CQDs silicon-based photodetectors can...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…In 2021, Shi et al reported on a PbS QD/polymethyl methacrylate (PMMA)/PbSe QD Si-based phototransistor, which PbS QDs as the filter layer, and PbSe QDs as the photosensitive layer in contact with the silicon channel, using PMMA to separate the filter layer from the photosensitive layer (Figure 9h). [154] Since QDs can integrate the optical filtering function directly into the photodetector cell, no additional optical filter is required for this type of device (Figure 9i). The spectral response range can be controlled by adjusting the particle size of QDs in the active layer.…”
Section: Phototransistormentioning
confidence: 99%
See 1 more Smart Citation
“…In 2021, Shi et al reported on a PbS QD/polymethyl methacrylate (PMMA)/PbSe QD Si-based phototransistor, which PbS QDs as the filter layer, and PbSe QDs as the photosensitive layer in contact with the silicon channel, using PMMA to separate the filter layer from the photosensitive layer (Figure 9h). [154] Since QDs can integrate the optical filtering function directly into the photodetector cell, no additional optical filter is required for this type of device (Figure 9i). The spectral response range can be controlled by adjusting the particle size of QDs in the active layer.…”
Section: Phototransistormentioning
confidence: 99%
“…i) Working principle of Si-based s-PD. Reproduced with permission [154]. Copyright 2021, The Royal Society of Chemistry.…”
mentioning
confidence: 99%
“…he detection of short-wave infrared (SWIR, 1 − 1.7 𝜇𝑚) wavelengths has significant applications including fiberoptic telecommunication [1], optical gas sensing [2], civilian and military applications [3], biosensors [4], night vision [5], and health monitoring systems [6], [7]. SWIR detection requires high-responsivity photodetectors (PDs) with high speed and low noise.…”
Section: Introductionmentioning
confidence: 99%
“…QDs have gained significant interest in optoelectronic devices such as photodetectors, solar cells, and energy storage devices . PbS QDs have great potential in the field of high-performance PDs due to their low-cost solution synthesis method, high quantum yield, high optical absorption coefficient, and high carrier mobility. PbS QDs are used in IR PDs due to their tunable band-gap energies and excellent optical properties, but they usually contain toxic elements and are unable to cover the vis band. Ag 2 S is a direct band-gap semiconductor (0.9–1.1 eV) with a vis–NIR spectral range. It has good chemical stability and optical properties.…”
Section: Introductionmentioning
confidence: 99%